George Eliot and Music - Gray, Beryl. author. aut Link
XII, 151 p.
Keywords: A treatise which explores the extent to which music played a role in the literary works of George Eliot. The author concentrates principally on "The Mill on the Floss", "Middlemarch" and "Daniel Deronda" and argues that music was an indispensable component of each of these works.